HER2-Positive Breast Cancer—Current Treatment Management and New Therapeutic Methods for Brain Metastasis - Hanna Miski; Kamila Krupa; Michał Piotr Budzik; Andrzej Deptała; Anna Badowska-Kozakiewicz (Biomedicines)
Background: Breast cancer can be classified based on the immunohistochemistry (IHC) phenotypes, defined by the presence or absence of the main IHC markers. IHC phenotyping is important as it determines the prognosis and guides treatment. For example, human epidermal growth factor receptor 2 (HER2) overexpression, which triggers cell growth and division, is observed in HER2-positive breast cancer. Methods: The standard treatment is based on trastuzumab plus pertuzumab in combination with taxane chemotherapy. The possibility of developing metastases depends on those phenotypes. Approximately 25–50% of patients with HER2-positive breast cancer experience brain metastases. This aspect is especially important, as 20% of those patients die as a result. Results: Through the years, many advanced therapies have been introduced to treat brain metastases, including whole brain radiotherapy, stereotactic radiosurgery, and a tyrosine kinase inhibitor (TKI), neratinib. Nonetheless, this still remains a therapeutic challenge. Conclusions: In this review, we focus on the treatment and efficiency of therapies targeting HER2-positive breast cancer, mainly concentrating on the current and newly developed treatment options for brain metastases, such as trastuzumab deruxtecan and tucatinib.